Persepsi Wisatawan Nusantara Terhadap Makanan Tradisional Dalam Perkembangan Wisata Kuliner di Kota Blitar, Jawa Timur - Kristiana, Nina Indra; Putra, I Nyoman Darma; Kumbara, A.A. Ngurah Anom (Program Studi Administrasi Perhotelan, 2023)
This research aimed to investigate the importance of traditional culinary in supporting the growth of culinary tourism in Blitar City, East Java. The study focused on the perception of local tourists toward traditional food and the role of the government and traditional food in tourism development. Data was collected using interviews, questionnaires, observations, and documentation. The data analysis was conducted using both descriptive qualitative and statistic descriptive methods. The findings revealed that the perception of local tourists toward traditional food and beverages in Blitar City was